IDENTIFIKASI UMKM (USAHAMIKRO KECIL MENENGAII) PETERNAKAN SAPI DI KECAMATAN TAWANGSARI KABUPATEN SUKOHARJO - Handayani, Sugiharti Mulya (Jurnal Ilmu-Ilmu Pertanian, 2011)
This study aimed to identify the practitioners of UMKM (Micro Small Medium Enterprise) cattle farming in Tawangsari Sub-District, Sukoharjo, taking 60 people as respondents by survey method. The results showed that the breeders: l) were of productive age;2) had 3 to 4 family members; 3) had junior high education level; 4), owned I-2 cattle; 3) were inactive in farmer groups 4) traditionally managed the business by implementing a simple technology 5) were mainly working as breeders; 6) were marketing in local markets with sales of Rp 500.000, -- Rp 1.000.000, - to be paid in cash; and 7) were not competing among breeders.